Does the trauma associated with out-of-home care transmit across generations? Evidence from the 1970 British Cohort Study during a major health pandemic. Issue 4 (29th April 2022) - Parsons, Sam; Schoon, Ingrid
Abstract : Objectives: Children with experience of out-of-home care (OHC) are at an increased risk of adverse outcomes in later life, including poorer levels of psycho-social adjustment. Less is known about the intergenerational transmission of the trauma associated with OHC and psychosocial outcomes in mid-adulthood, particularly during a major health pandemic. Design: To examine if there is evidence of intergenerational transmission of trauma associated with OHC in mid-adulthood, we used data from the 1970 British Cohort Study 2020 COVID-19 Survey. Participants: Cases were defined as cohort members (CMs) who had themselves experienced OHC (OHC1) and those whose mother reported to have been in OHC (OHC2). Among the 5320 CMs who participated in the second COVID-19 Survey, we have OHC information for n=4236. Our analytical samples range from n=2472 to 3864 depending on outcome: the largest sample comprised 105 (2.5%) CMs with direct OHC experience (OHC1), 93 (2.2%) CMs with a mother who had OHC experience (OHC2) and 3666 CMs with no OHC experience (OHC0). Outcome measures: Self-reported outcomes at age 50 included indicators of depression, health and psychological well-being. Multivariate logistic regression models control for socioeconomic childhood background and current circumstances. Results: Compared with the majority OHC0, the OHC1 group report higher levels of depression (OR 2.18 (95% CI 1.09 to 4.36) p<.05) and are at a greater risk of poor mental (OR 2.23 (95% CI 1.24 to 4.02) p<0.01) and general health (OR 3.32 (95% CI 1.65 to 6.67) p<0.001) during the pandemic. OHC2 was more than twice as likely to report poor mental health prepandemic (OR 2.52 (95% CI 1.37 to 4.64) p<0.01), but not during the pandemic. Conclusion: Children of care leaver mothers (OHC2) appear to be better adjusted than those who were themselves in care (OHC1), although compared with those without care experience (OHC0) both groups had an increased risk of poorer adult outcomes. However, the findings point to both continuity and discontinuity of disadvantage.